Frequency of HNF4A-P.I463V Variant in the Tunisian North-African Population and Its Relation with Diabetes Mellitus - Abdelbasset Amara; Ilhem Ben Charfeddine; Houda Ghédir; Ons Mamaï; Saloua Jemni-Yacoub; Larbi Chaieb; Ali Saad; Molka Chadli-Chaieb; Moez Gribaa (Tehran University of Medical Sciences, 2015)
Background: HNF4A-p.I463Vvariant, reported previously in two distinct families suspected of MODY-1, is assessed in this report to determine whether it is a mutation or a polymorphism (frequency >1%). Methods: 200 Tunisian healthy people were screened for the presence of HNF4A-p.I463V variant, using RFLP-PCR technique and sequencing. Then, the frequency of this variant was estimated in the Tunisian population and compared to other populations registered in genetic databases. We also performed in-silico analysis using PolyPhen2 and Mutation T@sting softwares to assess the probable effect of HNF4A-p.I463V variant. Results: HNF4A-p.I463V had a rare frequency in different populations and was found in 3 control subjects (1.5%) of the studied population. PolyPhen2 predicted that it is a polymorphism, whereas mutation T@sting suggested a probably affected mutant protein. Conclusion: HNF4A-p.I463V has a relatively high frequency (>1%) in our control cohort. It is also present in different ethnicities and in- silico analysis showed conflicting results. For these reasons, HNF4A-p.I463V should not be considered as a mutation responsible for MODY-1.